3D numerical simulation of a novel ventilated roof: thermal performance analysis and fluid flow behavior. (3rd July 2021) - Calati, Michele; Doretti, Luca; Zilio, Claudio; Mancin, Simone
Abstract : This paper presents a numerical simulation of a ventilated roof based on a novel plastic support especially designed to reduce the solar heat gains by improving the airflow distribution as compared to a traditional one. In order to evaluate the benefits of the new configuration, a 3 D numerical model was developed allowing for a deep understanding of the airflow distribution inside the ventilated roof channels. The simulations were performed by varying the solar irradiance from 600 to 1000 W m −2 assuming buoyancy-driven airflow. The investigation was conducted by comparing the new proposed ventilated roof assembly to the traditional layouts. In particular, two roof types were considered as benchmarks: an insulated roof and a non-insulated one. When compared to the traditional ones, the results revealed that the innovative ventilated roof led to a great reduction (up to 70%) of the total amount of solar heat gains for all the simulated scenarios.